Mouse Grueneberg ganglion neurons share molecular and functional features with C. elegans amphid neurons - Brechbühl, Julien; Moine, Fabian; Broillet, Marie-Christine (Frontiers in Behavioral Neuroscience, 2013)
The mouse Grueneberg ganglion (GG) is an olfactory subsystem located at the tip of the nose close to the entry of the naris. It comprises neurons that are both sensitive to cold temperature and play an important role in the detection of alarm pheromones. This chemical modality may be essential for species survival. Interestingly, GG neurons display an atypical mammalian olfactory morphology with neurons bearing deeply invaginated cilia mostly covered by ensheathing glial cells. We had previously noticed their morphological resemblance with the chemosensory amphid neurons found in the anterior region of the head of Caenorhabditis elegans (C. elegans). We demonstrate here further molecular and functional similarities. Thus, we found an orthologous expression of molecular signalling elements that was furthermore restricted to similar specific subcellular localisations. Calcium imaging also revealed a ligand selectivity for the methylated thiazole odorants that amphid neurons are known to detect. Cellular responses from GG neurons evoked by chemical or temperature stimuli were also partially cGMP-dependent. In addition, we found that, although behaviours depending on temperature sensing in the mouse, such as huddling and thermotaxis did not implicate the GG, the thermosensitivity modulated the chemosensitivity at the level of single GG neurons. Thus, the striking similarities with the chemosensory amphid neurons of C. elegans conferred to the mouse GG neurons unique multimodal sensory properties.